Habermas e o ofício docente como interação comunicativa - Rosa, Nilson Carlos da (2013)
This work aims to discuss the interaction communicative point of view of the teaching profession in the educacional scenarium complex and pluralist ocidentl societies. The idea of research is that the habermasianist concept of communicative acting allows us to think about teaching profession as interactive teaching. Basically this work tries to analise what contributions of Theory of Society and Theory of Communicative Acting of Habermas can bring to day s teaching nowadays. The research has a bibliographic aspect and is based on Habermas and Tardif works and discusses the contributions of the scholars Habermas. The starting point of the text is The Theory of Society of Habermas structured as a system and way of life Understanding it as model for complex societies. From that point on approaches the Theory of Communicative Interacting to the field of Educacion. In the third chapter the discussion is based on the ideas of Habermas and Tardif aiming the teaching profession as a communicative interaction based on the three dimension of the profession such as: the teachers knowledge, the pedagogic relationship and the professional development process